2011
DOI: 10.1007/978-1-61779-452-0_5
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Primary Astrocyte Cultures Devoid of Contaminating Microglia

Abstract: Microglia, resident phagocytic cells of the central nervous system, are frequent contaminants of astrocyte cultures. Unfortunately and not always fully appreciated, contamination by microglia can confound results of studies designed to elucidate the molecular mechanisms underlying astrocyte-specific responses. The paradigm described herein employs the mitotic inhibitor, cytosine β-D: -arabinofuranoside, followed by the lysosomotropic agent, leucine methylester, to maximally deplete microglia, thereby generatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 26 publications
2
23
0
Order By: Relevance
“…The proportion of microglia in rodent astrocyte culture may vary from 1% to 30% depending upon several factors that include animal age, species, region, culture medium, subculturing method and shaking 30 . In our cultures we observed approximately 6% of microglial contamination which is comparable with other reports 25 . If the intended use of the astrocyte culture is to study the role of hippocampal astrocytes in inflammation it is imperative to treat the cultures with 5 mM LME for 10 d to eliminate possible microglial contamination in the astrocyte cultures starting from DIV 3.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The proportion of microglia in rodent astrocyte culture may vary from 1% to 30% depending upon several factors that include animal age, species, region, culture medium, subculturing method and shaking 30 . In our cultures we observed approximately 6% of microglial contamination which is comparable with other reports 25 . If the intended use of the astrocyte culture is to study the role of hippocampal astrocytes in inflammation it is imperative to treat the cultures with 5 mM LME for 10 d to eliminate possible microglial contamination in the astrocyte cultures starting from DIV 3.…”
Section: Discussionsupporting
confidence: 93%
“…On the contrary, none of the cells were found to express MAP2 suggesting the culture was totally devoid of any neuronal contamination (Figure 3). The minor microglial contamination observed in our cultures is in accordance with other reports, wherein the authors reported a 5% microglial contamination in their primary cortical astrocyte cultures derived from 1 -3-day-old mouse pups 25 . Astrocytes possess a specific cytoarchitecture that allow them to respond to changes in their microenvironment including hypoxia.…”
supporting
confidence: 93%
“…000661) or xCT-deficient mice (43) (sut/sut; JAX; stock no. 001310) mouse pups as described (31,44). Dissociated cells were plated in multiwell plates (Falcon Primaria; BD Biosciences) or tissue culture dishes (BD Biosciences) in glial plating medium (see above).…”
Section: Methodsmentioning
confidence: 99%
“…Culture medium was replaced with fresh medium every 3rd day. Microglia were eliminated as previously described by Uliasz et al [22]. When confluent, the cells were dissociated using TrypLE (Life Technologies), pelleted by centrifugation at 500×g and re-plated in complete medium onto poly-D-lysine-coated plates at a density of 20,000 cells/cm 2 .…”
Section: Cortical Astrocyte and Neuronal Culturesmentioning
confidence: 99%